Enhanced Intermittent Modulation with Discontinuous Current Mode of a Three-Phase Dual-Active-Bridge Converter - Wen J.; Tan N.M.L.; Buticchi G.; Yang J.; Guenter S. (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper proposes an enhanced intermittent modulation (EIM) method with discontinuous current mode (DCM) to enhance power efficiency of a 700-V 20-kW three-phase dual-active bridge (3p-DAB) converter during light load operation. The 3p-DAB converter using traditional phase shift modulation (PSM) will lose soft switching feature under low load condition, resulting in significant reduction in power efficiency in low load condition. Simulation results of the non-ideal 3p-DAB converter using Simulink and PLECS software have shown that the proposed EIM-DCM modulation is effective in improving the light-load power efficiency. Moreover, an optimal trajectory with high power efficiency could be found by changing the non-power transfer duration of the proposed EIM-DCM. 2023 IEEE.